Effects of laser shock peening on the mechanisms of fatigue short crack initiation and propagation of AA7075-T651. (February 2021) - Sanchez, A.G.; You, C.; Leering, M.; Glaser, D.; Furfari, D.; Fitzpatrick, M.E.; Wharton, J.; Reed, P.A.S.
Highlights: Laser shock peening performed on AA7075-T651 to improve fatigue performance. XRD and incremental hole drilling show deep compressive residual stresses. 4-point bend testing and fractography show a change in fatigue regime and large increase in fatigue life. Modelling highlights sensitive balance between surface roughness, residual stress and micro-mechanisms of crack initiation. Abstract: A laser shock peening (LSP) treatment was performed on AA7075-T651 for maximum fatigue improvement. Surface and microstructural characterisation techniques (micro-hardness, SEM-EBSD, contact-profilometry) showed LSP surface modification was limited, and LSP generated deep compressive residual stresses above −300 MPa. Fatigue testing showed a two-order magnitude increase in overall life, due to the mechanism of crack initiation changing from surface second-phase particles to subsurface crack initiation dependent on the local stress field. Modelling highlights the sensitive balance between surface roughness (including LSP-induced pits) and residual stress on the micro-mechanism of crack initiation, and how this can be used to maximise fatigue life extension.